PESONA MORAL SASTRA POPULER PASCA TAHUN 2000-AN - Satriani, Irma; Ramadhani, Andi Reski; Salam, Aprinus; Dewi, Anita Candra (Universitas Hamzanwadi, 2025)
Personal morality is one of the important things in the existence of literature, not least in popular literature. Popular literature in Indonesia displays different moral faces from time to time. One of the dilemmas of moral issues is in presenting issues of ethnicity, religion, race, inter-group (SARA), and sex. This study questions how popular literature after the 2000s presents the morality of ethnicity, religion, violence, inter-group, and sex. These differences are possible because Indonesian society is increasingly educated and literate on the one hand, and when social media technology takes over